Kaposi's Sarcoma in an HIV and Covid-19 positive patient (Research, Society and Development, 2021)
Objective of this work is to report and discuss the case of a 61-year-old female patient, black, admitted to the University Hospital Maria Aparecida Pedrossian, diagnosed with Covid-19 and HIV, whose dental care together with the multidisciplinary team assistant, made the diagnosis of Kaposi's sarcoma, a cancer highly associated with immunocompromised patients with first appearance, most of the time, in the oral cavity, with systemic repercussions that can affect the evolution and clinical management of the case. Anatomopathological and immunohistochemical results confirmed the HIV diagnosis. During hospitalization patient presented clinical worsening and significant spread of the lesions, with the appearance of violaceous stains throughout the entire length of the head, neck, lower limbs, and gastrointestinal tract. There was no satisfactory therapeutic response, for this reason, palliative care was instituted, and cancer treatment was not performed.